Experimental study of the heat affected zone (HAZ) and surface roughness on laser beam cutting (LBC) on acrylic sheet - Faris, Suffian (2009)
Nowadays, laser beam is a practical and versatile tool for processing range of alloys, glasses, ceramics, composites, polymers and metal in manufacturing industries. Laser beam cutting (LBC) is achieved by the radiation emitted by a focused beam of coherent light with a assistance of a high pressure gas. Advantages of using laser beam cutting are, material with complex figures can be easily be cut by incorporating CNC motion equipment. High cutting speed, low distortion, very high edge quality and a minimal width of heat affected zone. It can sufficiently replace current existing techniques. LBC is different compared to the conventional machine tools that design for a particular purpose. There are number of parameters that plays important role in laser cutting processes. Each parameter will affect the processing operation. The significant parameter to be consider are laser power, cutting speed (delay time), nozzle gap, air pressure and cutting angle. This is because there is a significant relation between the parameters. Different in laser cut parameters will yield different type of results. In this project, sample of acrylic sheet with thickness of 3mm were cut using 0 laser cutting system with the variation of the five parameters. The effect of these five factors on surface roughness and width of heat affected zone have been studied. Data obtained was interpreted to develop graph to find the best combination of parameters on laser cut quality. Besides that relationship between laser power and delay time were also described. As a result for surface roughness research, the best combination of parameters was obtained. As for width of heat affected zone research, the best combination of parameters was obtained. Its means that all the parameters play a great role in produces high quality cut. To obtain better and precise results , environment effects such as air ventilation, air humidity, efficiency of laser beam machine and room temperature should be consider.